On the Relationship between Field Amplitude Distribution, Its Maxima Distribution, and Field Uniformity inside a Mode-Stirred Reverberation Chamber - M. A. García-Fernández; C. Decroze; D. Carsenat; N. Arsalane; G. Andrieu (International Journal of Antennas and Propagation)
A mode-stirred reverberation chamber (RC) is nowadays a commonly accepted performing tool for over-the-air (OTA) communication system evaluation, and their standardization is underway. Before performing active measurements of wireless communication systems using an RC, field uniformity inside the RC working volume has to be measured following the calibration method described in IEC standards 61000-4-21 and 61000-4-3, which requires 24 calibration measurements of field amplitude. In this contribution, we present the statistical laws that describe electromagnetic field maxima distribution, and based on them, a novel expression that could be useful to obtain a lower limit for the number of stirrer positions required at least to obtain a specific value for the normalized dispersion used to evaluate field uniformity with the IEC calibration method, being therefore of particular interest for OTA measurements.